Penguatan Keuangan Rumah Tangga sebagai Pertimbangan Persepuluhan dan Proporsi Kebutuhan Jemaat Kategorial Janda HBKP Malang - fitriasari, rizka; Nugraha, Adri Putra; Firdaus, Rizalnur (Jurnal Likhitaprajna, 2024)
The desire of members of the Widow Women category in presenting their income needs to be proportionately allocated so that household needs are still met. The purpose of this community service activity aims to open the categorical insights of Widowed Women in implementing the proportion of their income to meet their needs and fulfill their tithe offerings. This broader insight is also needed to strengthen the church's internal management in terms of finances. The consistent level of tithe offering contributes to the strength of the church in meeting its operational needs, and also meeting the spiritual needs of Christians in giving expressions of gratitude for the sustenance given by God Almighty. The community service method is carried out using classical simulations in terms of managing the proportion of ideal household needs so that tithing can be fulfilled. The results of this activity show that widows in the community of widowed mothers HKBP Malang in general seek their income in the allocation of church tithes